Cryptic species in the cosmopolitan Bugula neritina complex (Bryozoa, Cheilostomata). (24th October 2013) - Fehlauer‐Ale, Karin H.; Mackie, Joshua A.; Lim‐Fong, Grace E.; Ale, Ezequiel; Pie, Marcio R.; Waeschenbach, Andrea
<x xml:space="preserve">Abstract</x> Previous analyses of the mitochondrial gene cytochrome c oxidase subunit 1 (COI) and γ‐proteobacterial endosymbiont diversity have suggested that the marine bryozoan Bugula neritina is a complex of three cryptic species, namely Types S, D and N. Types D and N were previously reported to have restricted distributions along California (western USA) and Delaware and Connecticut (eastern USA), respectively, whereas Type S is considered widespread in tropical, subtropical and temperate regions due to anthropogenic transport. Here, Bayesian species delimitation analysis of a data set composed of two mitochondrial (COI and large ribosomal RNA subunit [16S]) and two nuclear genes (dynein light chain roadblock type‐2 protein [DYN] and voltage‐dependent anion‐selective channel protein [VDAC]) demonstrated that Types S, D and N correspond to three biological species. This finding was significantly supported, in spite of the combinations of priors applied for ancestral population size and root age. Furthermore, COI sequences were used to assess the introduction patterns of the cosmopolitan Type S species. Two COI haplotypes of Type S (S1a and S1d) were found occurring at a global scale. Mantel tests showed correlation between these haplotypes and local sea surface temperature tolerance. Accordingly, the distributions of Type S haplotypes may reflect intraspecific temperature tolerance variation, in addition to the role of introduction vectors. Finally, we show that the Type N may also have been introduced widely, as this species was found for the first time in Central California and north‐eastern Australia.